Phase I Study of Celecoxib with Concurrent Irinotecan, Cisplatin, and Radiation Therapy for Patients with Unresectable Locally Advanced Non-Small Cell Lung Cancer - Komaki, Ritsuko; Wei, Xiong; Allen, Pamela K.; Liao, Zhongxing; Milas, Luka; Cox, James D.; O'Reilly, Michael S.; Chang, Joe; McAleer, Mary F.; Jeter, Melenda; Blumenschein, George R.; Kies, Merrill S. (Frontiers in Oncology, 2011)
Purpose: Preclinical findings suggest that adding targeted therapies to combination radiation-chemotherapy can enhance treatment efficacy; however, this approach may enhance normal tissue toxicity. We investigated the maximum tolerated dose, dose-limiting toxicities, and response rate when the selective cyclo-oxygenase-2 inhibitor celecoxib is added to concurrent irinotecan, cisplatin, and radiation therapy for patients with inoperable stage II-III non-small cell lung cancer. Methods and materials: Eighteen patients were analyzed in a phase I clinical dose-escalation trial. Celecoxib was given daily beginning 5 days before radiation followed by maintenance doses for 12 weeks. Toxicity was graded with the Common Terminology Criteria for Adverse Events V3.0 and response with the World Health Organization system. Primary endpoints were maximum tolerated dose of celecoxib and treatment toxicity; secondary endpoints were response and survival rates. Results: The maximum tolerated dose of celecoxib was not reached, in part owing to discontinuation of the drug supply. At doses of 200 or 400 mg/day, no patients experienced any dose-limiting toxicity (acute grade ≥4 esophagitis or pneumonitis, neutropenic fever or thrombocytopenia requiring transfusion, or acute grade ≥3 diarrhea). Grade 3 toxicities were leukopenia (5 patients), fatigue (3), pneumonitis (2), dyspnea (1), pain (1), and esophageal stricture (1). Interestingly, pulmonary fibrosis (a late toxicity) was no more severe in the higher-dose (400-mg) group and may have been less common than in the lower-dose group. The clinical response rate was 100% (8 complete, 10 partial). Two-year rates were: overall survival 65%; local-regional control 69%; distant metastasis-free survival 71%; and disease-free survival 64%. Conclusions: Although preliminary, our results suggest that adding celecoxib to concurrent chemoradiation for inoperable NSCLC is safe and can improve outcome without increasing normal tissue toxicity.